A Concept of Islamic Notary as Registrar on Sharia Contract: al-Muwaththiq Perspective - Iza Hanifuddin; Moh. Ihsan Fauzi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
Public notary officials are authorized to make authentic deeds. The notary’s deeds are significant for business activities, including Sharia contracts in Sharia banking. The notary paradigm derived from conventional concepts is undoubtedly different from the concept of sharia banking based on sharia principles. Thus, notaries often do not know these principles unless they only concern the contract's validity, which is still conventional. This research aimed to answer the void of Sharia notary law. Islam has the concept of al-Muwaththiq, similar to a notary mainly requiring personality and expertise, especially related to Islamic law. On the other hand, Law Number 2 of 2014 concerning Notary Official Changes also becomes a notary basis in every operation, including contracts in Sharia banking. This research employed library study approaches to explore the notaries’ competence in the concept of al-Muwaththiq. The results and discussions showed that notaries making authentic deeds in Sharia banking must have sharia competence as excavated from the concept of al-Muwaththiq since their incompetence will impact Islamic law validity. Moreover, Notaries must also follow the applied positive rule of law because Sharia banking, as a sub-system of national banking, is also subject to state-regulated regulations.